2020
DOI: 10.3390/plants9080961
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Applications and Uses of Thymus in the Food Industry

Abstract: Thyme is one of the most important medicinal plants because of its ethnopharmacological relevance and high content of bioactive compounds. This review focuses particularly on thyme as an alternative natural antioxidant and antimicrobial with potential use in the food industry. This is in line with the preferences of the current consumer, who demands healthier and more natural products. Different studies have concluded that the use of thyme increases stability and reduces lipid oxidation during the shelf-life p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 176 publications
4
107
0
2
Order By: Relevance
“…Furthermore, it is suggested that positive effects of galactagogues on milk production may be due to the decrease in circulating biogenic amines such as histamine, tryptamine and tyramine in the blood, which are known to cause the excessive release of catecholamines, leading to a reduction in milk production as well as causing indigestion by inhibiting ruminal mobility and absorption [ 52 ]. Other researchers have shown that herbal essential oils can act as galactagogues by enhancing prolactin production and releasing somatotropins, resulting in increased glucose levels in the udder and improved milk production [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is suggested that positive effects of galactagogues on milk production may be due to the decrease in circulating biogenic amines such as histamine, tryptamine and tyramine in the blood, which are known to cause the excessive release of catecholamines, leading to a reduction in milk production as well as causing indigestion by inhibiting ruminal mobility and absorption [ 52 ]. Other researchers have shown that herbal essential oils can act as galactagogues by enhancing prolactin production and releasing somatotropins, resulting in increased glucose levels in the udder and improved milk production [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The properties and composition of oregano and thyme have been well investigated. It was reported that their essential oils possess anti-bacterial, anti-fungal, anti-inflammatory and antihistaminic effects [ 54 , 55 ]. Oregano and thyme essential oils increased mammary gland development in rats, followed by a higher milk yield at different stages of lactation [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…New trends in the use of Moringa oleifera in bakery products focus on the preservation of its antioxidant power and on the use of dietary supplements in case of nutritional deficiency situations. In this context, according to the nutritional evaluation, it can be concluded that these components can be used as nutraceuticals [ 95 , 96 , 97 , 98 ]. The study of molecules of protein nature with bioactive effects on human health, such as antiproteolytic, procoagulant, antidiabetic, antihypertensive and anti-inflammatory properties, opens up new strategies for the design of nutritional supplements and the design of functional foods.…”
Section: New Trendsmentioning
confidence: 99%
“…Thymus capitatus contains bioactive compounds such as phenols, phenolic acids, terpenes and flavonoids [36][37][38]. Thymus capitatus is containing a rich source of vitamins, particularly vitamin C, vitamin A, and vitamin B6.…”
Section: Introductionmentioning
confidence: 99%